PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN INPRES NOMOR 3 TAHUN 2000 TENTANG KOORDINASI PENANGGULANGAN MASALAH PERTAMBANGAN TANPA IZIN DI DESA KASANG LIMAU SUNDAI KECAMATAN KUNTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Gustina, Yolanda; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was motivated by the existence of mining without a permit in the village of Kasang Limau Sundai, is an acronym for (Gold Mining Without Permit) which is carried out by some people and other elements. The formulation of the problem in this study is how the community's perception of the implementation of Presidential Instruction Number 3 of 2000 concerning the Coordination of Handling Problems of Mining Without Permits in Kasang Limau Sundai Village, Kuantan Hilir Seberang District. The research objective was to determine the community's perception of the implementation of Presidential Instruction Number 3 of 2000 concerning the Coordination of Handling Problems of Mining Without Permits in Kasang Limau Sundai Village, Kuantan Hilir Seberang District. Data collection techniques in this study were observation, interviews and documentation. There were 8 respondents in this study, namely: 2 village government officials, 2 traditional and community leaders, 4 community members. The data analysis technique used qualitative methods. The results of this research can be explained that the community's perception of the efforts made by the government in dealing with mining problems in Kasang Limau Sundai Village, where mining activities have positive and negative impacts. The government's obstacle in dealing with the problem of PETI activities is the lack of legal apparatus involving the government as well as traditional leaders and communities in the village concerned, besides that the level of community awareness is still lacking about the impact that will be caused.Key Words: Public Perception, Presidential Instruction No. 3 Year 2000, Overcoming PETI